Effect of Social Media’s Role in Public Political Opinion on 2024 General Election in Indonesia - Jasmine Ariani; Nieldya Nofandrilla (JOM, 2026)
Political campaigns' communication strategies increasingly rely on social media especially in the period leading up to the 2024 General Election, this Political Communication research has had a prominent position in the academic fields of both communication studies and political science. So, this study aims to examine the influence of social media on the formation of public political opinion, particularly in the context of the 2024 General Election in Indonesia. Drawing on the Uses and Gratifications Theory, this research emphasizes the active role of individuals in selecting, engaging with, and responding to political content on social media platforms. A quantitative approach was employed using an online survey distributed to 100 active social media users aged 17–40 years. The study analyzes the effects of Exposure to Political Content (X1), Social Media Interaction (X2), and Content Virality (X3) on Public Political Opinion (Y), with Sentiment (Med1) and Changes in Political Opinion (Med2) as mediating variables. Data were analyzed using multiple regression and mediation analysis. The results indicate that all independent variables have a positive and significant effect on public political opinion. Furthermore, sentiment and changes in political opinion significantly mediate the relationship between social media use and opinion formation. The findings also reveal that visual content, particularly short-form videos and infographics, plays a dominant role in influencing political perspectives, especially among younger users. Although many users do not actively express their opinions, passive exposure to political content still contributes significantly to shaping their political views. That means social media plays a crucial role in shaping public political opinion through both direct and indirect mechanisms, highlighting the importance of user engagement and psychological processes. The findings contribute to the understanding of digital political communication and emphasize the need for improved digital literacy to support a more informed and balanced public discourse.